Role of Carboxy Terminal Propeptide of Type I and Type III Procollagen (PICP and PIIICP) Toward the Severity Degree of Mitral Valve Regurgitation in Children’s Rheumatic Heart Disease - Suwarniaty, Renny; Rohman, Mohammad Saifur; Hernowati, Tinny Endang; Barlianto, Wisnu (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Rheumatic heart disease (RHD) is recognized as a heart disease that occurs as a result of sequelae in acute rheumatic fever (ARF), characterized by the occurrence of defects in the heart valves. The most common manifestation of childhood RHD is mitral regurgitation (MR). The role of inflammation and oxidative stress in RHD also involves several components consisting of carboxy-terminal pro-peptide of Type I procollagen (PICP) and carboxy-terminal pro-peptide of Type III procollagen (PIIICP). AIM: The aim of this study was to know whether PICP and PIIICP can be used to measure the severity level of mitral valve regurgitation. METHODS: This research is considered as descriptive-analytic research, and using cross-sectional analysis. Forty RHD patients underwent echocardiographic examinations to measure Wilkin and effective regurgitant orifice area scores. Patients were classified into ARF without valve abnormalities, mild, moderate, and severe MR. PICP and PIIICP were with ARF through venous blood and ELISA was examined. Data were analyzed by employing SPSS 22 with p = 0.05). Wilkins scores and PICP levels have a regression coefficient of 0.296 with a p-value of 0.032. RESULTS: There was a significant difference in PICP level among the studied sample groups with a p = 0.012, (p < 0.05), with insignificant difference in PIIICP level among sample groups with a p = 0.083, greater than α = 0.05 (p > 0.05). Wilkins scores and PICP level have a regression coefficient of 0.296 with a p = 0.032 (p < 0.05), while PIIICP level has a regression coefficient of 0.093 with a p = 0.568 (p > 0.05). CONCLUSION: There is no significant increase indicated on PIIICP level, but PICP level indicates a significant increase in RHD group with severe mitral valve abnormalities. PICP can be used to measure the severity level of mitral valve regurgitation.